กำหนดการเชิงเส้นเพื่อเพิ่มประสิทธิภาพสำหรับการใช้ทรัพยากร - ทรงยศ ไทยงามศิลป์ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
In Real Time Strategy (RTS) games, players must use strategy to create and control units and structures to destroy opponents. Resources are essential in building things, which will allow players to fight against their opponents. These resources are gathered by special units on the map. In addition, players must also develop technology and a base to strengthen their own units and structures. All of these are important processes that players need to consider when playing RTS games. This project is to create a mathematical model to find the order of constructing different types of units that gives the highest total attack power during a specified time. Usually, the order of constructions is based on player’s experience and this may be inefficient. The author therefore has gathered various limitations to create a mathematical model to solve the problem using linear programming.